PELAKSANAAN PENEGAKAN HUKUM TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA YANG DILAKUKAN OLEH ANGGOTA KEPOLISIAN DI RESORT INDRAGIRI HILIR - Dara Thia Ardiyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Policing is essentially a function of government and institutions engaged in themaintenance of security and public order. As a police agency or organization has theduty and the authority to maintain security and public order, enforce the law and provideprotection, guidance and service to the community. It is unfortunate that in fact inIndragiri Hilir regency, some police members involved in criminal cases is drug abuse.Background as described above, the authors are interested in doing research entitledImplementation of Law Enforcement Crime Narcotics Abuse committed by policemembers at the Resort Indragiri Hilir. In this study aims to determine how the lawenforcement abuse of narcotic offenses committed by police members at Resort IndragiriHilir, to determine barriers to law enforcement abuse of narcotic offenses committed bypolice members at Resort for Indragiri Hilir and criminal law enforcement abusenarcotics made by Members of the Police In Resort Indragiri Hilir. Terms of the methodused, this research can be classified in juridical sociological research, because in thisstudy the authors conducted research in the location directly by examining theapplication of the law. The research was conducted at the police station Indragiri Hilir,sources of data used are secondary data, primary data and secondary data while datacollection techniques with interviews and literature study. The collected data was thenanalyzed qualitatively by using the deductive method of analyzing the problems of ageneral nature then specifically drawn to the conclusion based on existing theories.From the research, there are three main things that can be concluded that theimplementation of the law enforcement drug abuse by police officers carried outseparately by 2 (two) first mechanism criminal proceedings conducted in public courtproceedings and both the Police Code. Barriers in law enforcement drug abuse by policemembers in the Police Jurisdiction Resort Indragiri Hilir, namely external and internalbarriers. Efforts to overcome obstacles in the mitigation Narcotics Abuse By Police InMember Jurisdiction Indragiri Hilir Police Resort is the first public education to bothhuman resource development and approach to the suspect, the third mapping, routinepatrol and patrol equipment and the addition of four transparency in law enforcement.Based on the conclusions the authors draw up suggestions that Indragiri Hilir PoliceStation are expected to continue to maintain a commitment to law enforcement efforts toits members without discrimination and should give strict punishment to members whocommit drug abuse.Keyword: Implementation - Law Enforcement - Drug Abuse - Members of the Police